2004
DOI: 10.1093/brain/awh126
|View full text |Cite
|
Sign up to set email alerts
|

Early development of multiple sclerosis is associated with progressive grey matter atrophy in patients presenting with clinically isolated syndromes

Abstract: While brain atrophy occurs early in the clinical course of multiple sclerosis, exactly how early, which tissues are affected and the rate at which early atrophy occurs are unclear. Regional brain atrophy was investigated in 58 patients recruited within 3 months of onset of a clinically isolated syndrome (CIS) suggestive of multiple sclerosis, who were followed-up for 3 years. At 3 years, 31 subjects had developed multiple sclerosis as defined by the McDonald criteria, while 27 had not (13 had MRI-visible brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
308
5
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(348 citation statements)
references
References 28 publications
32
308
5
3
Order By: Relevance
“…22 No significant differences were found in whole-brain, global GM, WM, and/or cortical volumes between the 2 groups. This confirms the results of some recent studies that showed that selective regional, but not global, atrophy occurs from clinical onset to conversion to clinically definite MS. [17][18][19][20] This study provides strong evidence that regional GM atrophy is exclusively confined to the SDGM and not to cortical regions in the first 4 years of disease duration. Our findings suggest, therefore, that future studies should concentrate more on understanding the pathogenetic mechanisms leading to selective SDGM rather than to cortical GM damage in patients with early RRMS.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…22 No significant differences were found in whole-brain, global GM, WM, and/or cortical volumes between the 2 groups. This confirms the results of some recent studies that showed that selective regional, but not global, atrophy occurs from clinical onset to conversion to clinically definite MS. [17][18][19][20] This study provides strong evidence that regional GM atrophy is exclusively confined to the SDGM and not to cortical regions in the first 4 years of disease duration. Our findings suggest, therefore, that future studies should concentrate more on understanding the pathogenetic mechanisms leading to selective SDGM rather than to cortical GM damage in patients with early RRMS.…”
Section: Discussionmentioning
confidence: 59%
“…[5][6][7] More recently, research has focused on determining the extent of GM pathology at the first clinical event in patients presenting with CIS [8][9][10][11][12][13][14][15][16] or on its evolution with conversion to clinically definite MS. [17][18][19][20] It has been reported that global GM volume measures are not sensitive enough to detect GM atrophy at the time of the initial attack.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, neuroimaging studies revealed microglia activation with minimal inflammatory cell infiltrates in proximity of cortical axonal transections [19]; this gray matter abnormality occurs surprisingly early and correlates much better with permanent disability, demonstrating that microglia activation in gray matter correlates with neuron loss and MS onset ( [37,51,201,230]). …”
Section: The Eae Animal Modelmentioning
confidence: 99%
“…MRI-based atrophy studies often focus on the brain, and loss of both gray matter (11,12) and white matter (13) has been shown in MS. Similarly, tissue loss in the spinal cord has been investigated in MS (7,8,10,14 -16), although less extensively than brain tissue loss, even though 90% of MS patients have spinal cord pathology (17).…”
mentioning
confidence: 99%